Teaching as a profession. A study on motivations of secondary education teachers in the State of Mexico - Mejía Bricaire, Jorge (2024)
The objective of this article was to carry out an analysis of the motivations that guided secondary education teachers to choose teaching as a profession within the framework of the Professional Teaching Service. The methodological approach was qualitative; the data collection instruments were the in-depth interview. Twenty-six interviews (12 women and 14 men) were conducted with graduates of Higher Education Institutions, Normal Schools (public) and Universities (public and private). The field work was carried out from October 2019 to July 2020 in the State of Mexico. The interpretation of the information was made from the structural analysis of stories to understand the motivations of people to choose teaching as a profession. This, in the midst of changes made to educational public policies in 2013, which modified the process of admission to teaching in the public sector. The main findings were that, in people graduated from Normal Schools, intrinsic and altruistic motivations predominate. And, to a lesser extent, the improvement of learning conditions and overcoming the inequalities of their students. In university graduates, extrinsic motivations prevail due to the economic benefits of being employed in the public sector. By way of conclusion, the motivations to be a teacher is not only a matter of vocation or altruism, but of job opportunity. It is opportune to integrate critical perspectives such as the gender approach to broaden the frameworks of analysis on the motivations for choosing teaching as a profession.